The Scientometrics and Information Retrieval: Bridging Weak-Link Between Technology and Performance - I Wayan Wirga; I Wayan Sukarta; Ida Bagus Sanjaya (Journal of International Conference Proceedings, 2022)
Studies over the past 20 years have shown that the alignment between technology utilization and business performance is a widespread and unexplored problem, especially in SMEs. While significant progress has been made to understand alignment, research on IT alignment is still plagued by several problems. This study aims to find patterns of the relationship between the role of technology and business performance through visual trends by identifying the keywords technology and business performance to find and identify related articles in the Scopus database that published from 2002 to 2022. The findings are visual trends increasing number of publications each year, authors, and subject area articles, keywords, and authorship networks. This literature review provides evidence that technology attracts academic researchers to make policy-relevant.